Tail Risks Across Investment Funds - Jerchern Lin (Finanse i Prawo Finansowe)
The purpose of the article. Managed portfolios are subject to tail risks, which can be either index level (systematic) or fund-specific. Examples of fund-specific extreme events include those due to big bets or fraud. This paper studies the two components in relation to compensation structure in managed portfolios.